Reforming Drug Price Regulation: Using Tools That Work - Deborah Williams MS; Steven C. Zima MBA; Brian J. Miller MD, MBA, MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Drug pricing reform to increase affordability has historically relied on increases in regulation often with a focus on administrative pricing for public programs in order to try to lower drug costs. This paper examines the consequences of this strategy, pointing out that regulated prices fail to drive affordability, create unintended, hidden costs to the system, and drive demand for a body of ever-growing regulatory interventions to address shortfalls created by prior policies. Within this context, the paper examines examples of regulations affecting large percentages of government payments the Medicaid Drug Rebate, the Inflation Reduction Act Maximum Fair Price, and the Average Sales Price formula in Medicare B enumerating how each of these programs that direct funds to Medicare or Medicaid only create hidden systematic costs when considered from the total market perspective. Next, a new paradigm for drug pricing reform philosophy is suggested, with a focus on market-based interventions to reform existing government regulation aimed at improving competition and consider examples of effective private market policies including co-insurance/copayment reform, private formularies, specialty pharmacies, and value-based contracting. The paper concludes by arguing that shifting from a programmatic view of affordability to an understanding of the regulatory effect on costs in the drug market, including regulatory burden reduction, is the best way to drive affordability for payers and thus ultimately for employers and consumers.